Response: Between Economics and Sociology: The New Path of Deterrence - Kahan, Dan M. (1997)
The explosive collision of economics and sociology has long illuminated the landscape of deterrence theory. It is a debate as hopeless as it is spectacular. Economics is practical but thin. Starting from the simple premise that individuals rationally maximize their utility, economics generates a robust schedule of prescriptions - from the appropriate size of criminal penalties,1 to the optimal form of criminal punishments, to the most efficient mix of private and public investments in deterrence. Yet it is the very economy of economics that ultimately subverts it: its account of human motivations is too simplistic to be believable, and it generates policies too severe to be just. Sociology is rich but impractical. Absorbing all the complexity of the world as it is, it supplies breathtakingly elaborate accounts of why individuals turn to crime - from the criminogenic properties of poverty to the self-reinforcing culture of criminality. But this elaborate account yields little usable policy guidance; by now it's clear that our society has neither the political will nor the socialscientific know-how to eradicate the root causes of crime. What's needed is a third way, one that combines the virtues of both economics and sociology without succumbing to the vices of either. If such an approach cannot be fashioned, the idea of deterrence might continue to function as a politically charged creed or as an absorbing focus for abstract formal models, but it will cease to furnish a practical framework for solving America's crime problem on morally acceptable terms. My goal in this essay is to call attention to an emerging body of criminal-law scholarship that I believe has the potential to chart a new course between sociology and economics. These works seek to enrich the standard economic conception of deterrence through attention to social norms, a concept that has figured prominently in other fields of law. Although they employ a diverse array of terms - from social organization, to moral credibility, to social meaning, to social influence - these works all stress the influence between law and shared values as an important explanation for the extent of crime